Habitat use patterns and food habits of the Kashmir red deer or Hangul (Cervus elaphus hanglu) in Dachigam National Park, Kashmir, India. Issue 1 (2nd January 2016) - Ahmad, K.; Qureshi, Q.; Agoramoorthy, G.; Nigam, P.
Abstract : The last surviving wild population of the Kashmir red deer ( Cervus elaphus hanglu ) or Hangul inhabits the Dachigam National Park located near Srinagar city of Kashmir, India. This paper presents data from February 2001 to December 2009 on habitat use patterns and food habits of the Kashmir red deer. Investigations based on surveys along trails indicate that Hangul showed significant differences in the use of different habitat types ( F  = 6.49; P  = 0.001) between seasons. Males showed significant differences in habitat utilization both within a season ( F  = 3.63; P  ≤ 0.013) and between seasons ( F  = 1.50; P  ≤ 0.087). Females showed differences in their habitat use within season but not between seasons ( F  = 14.771; P  ≤ 0.577). Surveys showed the deer predominantly using the lower and middle altitudes (1700–1900 m and 1900–2300 m) with no significant gender differences. The riverine and mixed oak forests showed the highest mean deer pellet density/ha (153.71 ± 173.43, n  = 418 and 188.60 ± 56.41, n  = 114, respectively). The grassy/rocky cliff habitat showed the lowest mean pellet density/ha (55.92 ± 18.32, n  = 228). The Hangul diet constituted mainly of dicotyledonous shrubs and trees (45.45 and 80.77%), forbs/herbs (36.36 and 19.23%), monocotyledon grasses and herbs (18.18 and 16.22%) in spring and winter, respectively. Summer diet comprised 42.86% forbs, 19.05% grass/sedges and 38.10% browses. In autumn, Hangul fed mainly on dicotyledonous shrubs. The habitat use patterns of Hangul are comparable with those of the European red deer and are influenced by availability of food, cover, shelter, altitude, slope, aspect and the level of disturbance. The habitats with ideal conditions for utilization but with a meager disturbance were avoided by Hangul. Recommendations are given for better and effective management, protection and conservation of this small and isolated population of red deer.